CONHECIMENTO DOS PROFISSIONAIS DAS UNIDADES BÁSICAS DE SAÚDE DE ANÁPOLIS-GO SOBRE A PREVALÊNCIA DE DEFICIÊNCIAS NAS POPULAÇÕES ADSCRITAS KNOWLEDGE OF PROFESSIONALS OF BASIC HEALTH UNITS ON THE PREVALENCE OF DISABILITIES IN ADSCRIPT POPULATIONS - Ana Paula Moreira Reis; Frederico de Souza Jaime; Felipe Jorge de Souza; Glenda Caroline Oliveira Ferreira; Thaís Maia Fernandes; Vanessa Cristina de Sousa Machado; Victor Clarindo Nominato Ribeiro; Júlia Maria Rodrigues de Oliveira (UniEVANGÉLICA, 2017)
Objectives: To identify the knowledge of professionals from Basic Health Units on the prevalence of physical, hearing and visual disability in populations includedenrolled between January 2013 and December 2014. Methods: A quantitative cross-sectional study was carried out with the professionals of the Basic Health Units In the municipality of Anápolis- GO. Results: It was observed that 40% of disabled persons attending the UBS in Anápolis in 2015 had visual impairment, followed by physically disabled (36%) and hearing disabled (24%). As for infrastructure resources adapted to service the handicapped, it has been observed that 60% of Basic Health Unities surveyed have ramps, 26% have adapted toilets, 17% have tactile floors, 5% adapted offices and 2%, the adjusted dental chair. Conclusion: It was concluded that the professionals units do not really know the prevalence of people with disabilities in their coverage areas.